Human Factors Engineering: Enhancing User Experience in Mechanical Systems - Joshi, Puneet (Journal of Advanced Research in Mechanical Engineering and Technology, 2024)
In an era dominated by technological advancements, the interaction between humans and mechanical systems is pervasive, encompassing a wide spectrum from consumer electronics to industrial machinery. Human Factors Engineering (HFE), also known as ergonomics, is a critical interdisciplinary field that optimizes these interactions to enhance safety, efficiency, and user satisfaction. By integrating principles from psychology, engineering, physiology, and industrial design, HFE ensures that systems are designed to align with human capabilities and limitations. This paper explores the significance of HFE, emphasizing its role in bridging the gap between complex technology and its users. It delves into the core principles of HFE, such as anthropometry, biomechanics, cognitive ergonomics, environmental ergonomics, and human-computer interaction, and examines the systematic process of applying these principles through user research, task analysis, design, prototyping, and usability testing. The paper also highlights the multidisciplinary nature of HFE, involving collaboration among experts from various fields, and discusses the ethical considerations essential for ensuring safety, privacy, accessibility, and usability. By presenting detailed applications of HFE across industries—ranging from consumer products and automotive design to industrial machinery, medical devices, aerospace, and public transportation—this paper underscores the pivotal role of HFE in enhancing safety, efficiency, and user experience. Additionally, it addresses the challenges in implementing HFE principles and outlines future directions, including adaptive interfaces, virtual and augmented reality, human-AI collaboration, inclusive design, and sustainable practices. Through case studies of the Tesla Model S, Boeing 787 Dreamliner, and Apple iPhone, the paper illustrates the tangible benefits of integrating HFE into mechanical system design, emphasizing its growing importance in creating systems that are not only functional but also user-friendly and attuned to human needs.